Comportamento de pessoas com hipertensão arterial : estudo fundamentado no modelo de crenças em saúde - Guedes, Maria Vilani Cavalcante (2005)
The chronic sickening requires a change or acquisition on people’s health behavior. In hypertension the behaviors involve changes in lifestyle. The prevalence of the disease, its cardiovascular complication risks, with possibilities of temporary or permanent sequels and death by difficulty in following the treatment, has concerned researchers around the world. The aim of this study is to evaluate the behaviors and beliefs of the people who suffers from blood hypertension, according to the Health Belief Model, and to identify how these people realize the risks involved on its complication: the susceptibility and severity. A sectional study was carried out with a population of 103 adult clients. They all suffer from arterial hypertension and were subscribed in the Hypertension Control Program for at least one year, having attended a minimal of seven consultations during the year. They freely accepted to participate in the study. The data was collected from August to December 2004 in a Municipal Health Center in Fortaleza – CE. Two different forms were used. One of them based in the Health Belief Model and the other was used to classify the participants relating to their following of the treatment. The statistic analysis was made with qui-square test, the Fisher-Freman-Halton with p < 0,005 and the Pearson and Rho Spearman’s coefficients. The results presented a group with 76.7% of women; the age of its members varied from 22 to 80 (average of 57,1 + 11,1); 29.1% of them have studied only for four years and five of them were illiterate; the average family income was of R$395,00; their diagnosis and treatment time ranged from one to 25 years and accompaniment from one to 16 years; 84.5% of them had records of cardiovascular disease in the family; 27.2% were with BMI between 18 and 24.9 kg/m2; 49 had the recommended values of waist circumference to women and men; 25.9% of the women were very good at following the treatment and 4.9% completely followed it. The group studied showed behavior that favors the following of the treatment; beliefs in the susceptibility to complications; in the disease severity; in the benefits of the treatment; in the barriers and in the stimulus to action. The results showed a statistically significant association between behavior and the following of the treatment (p=0,001); BMI (p=0,045); in the dimension severity and blood pressure < 140 x 90 mm Hg (p= 0,048 for SBP; p= 0,001 for DBP); with time of treatment (p= 0,027); following of the treatment and women waist circumference (p=0,001); following of the treatment and BMI (p=0,012); between benefits and the guidance following (p=0,001); the help of guidance during the treatment (p=0,013); the possibility of controlling blood pressure (p=0,001) and between barriers and schooling (p=0,024). The Pearson and Rho Spearman’s coefficients showed statistically significant correlations between averages of blood pressure (SBP e DBP) (p= 0,001) and (p= 0,023) respectively; weight (p=0,010) and (p=0,007) and diagnosis time (p=0,028) and (p=0,012); the following of the treatment (p=0,000) and (p=0,000) respectively. It was concluded that the group has behaviors and beliefs related to the disease severity, the treatment benefits, and it recognizes barriers to the treatment, but they have difficulty following the treatment.